CACCI country profile Tajikistan - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Tajikistan, one of the least urbanized countries in Central Asia, is prone to natural disasters, disruptions in rainfall, rising temperatures, reductions in glacial cover, and extreme weather events. Agriculture and energy sectors are the highest emitters of greenhouse gases. The Government of the Republic of Tajikistan acknowledges the problems and risks posed by climate change and is working to address them. One critical step is the submission of the updated Nationally Determined Contributions (NDCs) in 2021, which proposes efforts to support sustainable and efficient development, taking into consideration climate change and related environmental and socioeconomic challenges for the period 2020–2030. An NDC Implementation Plan was developed last year, which presents the key steps to be taken and the implementation period for each. The Committee for Environmental Protection under the Government of the Republic of Tajikistan (CEP) is the authorized policymaking and coordination body for climate change related activities and has created an NDC Secretariat for administrative and stakeholder engagement support. Some of the main challenges in efficiently adopting climate change measures include legal and institutional obstacles and lack of sufficient and appropriate technical capacity in the country.